Lava-ice interactions during historical eruptions of Veniaminof Volcano, Alaska and the potential for meltwater floods and lahars - Christopher F. Waythomas; Benjamin R. Edwards; Thomas P. Miller; Robert G. McGimsey (Natural Hazards, 2023)
Veniaminof Volcano on the Alaska Peninsula of southwest Alaska is one of a small group of ice-clad volcanoes globally that erupts lava flows in the presence of glacier ice. Here, we describe the nature of lava-ice-snow interactions that have occurred during historical eruptions of the volcano since 1944. Lava flows with total volumes on the order of 0.006 km 3 have been erupted in 1983–1984, 1993–1994, 2013, and 2018. Smaller amounts of lava (1 × 10 −4 km 3 or less) were generated during eruptions in 1944 and 2021. All known historical eruptions have occurred at a 300-m-high cinder cone (informally named cone A) within the 8 × 10-km-diameter ice-filled caldera that characterizes Veniaminof Volcano. Supraglacial lava flows erupted at cone A, resulted in minor amounts of melting and did not lead to any significant outflows of water in nearby drainages. Subglacial effusion of lava in 1983–1984, 2021 and possibly in 1944 and 1993–1994 resulted in more significant melting including a partially water-filled melt pit, about 0.8 km 2 in area, that developed during the 1983–1984 eruption. The 1983–1984 event created an impression that meltwater floods from Mount Veniaminof’s ice-filled caldera could be significant and hazardous given the large amount of glacier ice resident within the caldera (ice volume about 8 km 3 ). To date, no evidence supporting catastrophic outflow of meltwater from lava-ice interactions at cone A has been found. Analysis of imagery from the 1983–1984 eruption shows that the initial phase erupted englacial lavas that melted ice/snow/firn from below, producing surface subsidence outward from the cone with no discernable surface connection to the summit vent on cone A. This also happened during the 2021 eruption, and possibly during the 1993–1994 eruption although meltwater lakes did not form during these events. Thus, historical eruptions at Veniaminof Volcano appear to have two different modes of effusive eruptive behavior, where lava reaches the ice subglacially from flank vents, or where lava flows are erupted subaerially from vents near the summit of cone A and flow down the cone on to the ice surface. When placed in the context of global lava-ice eruptions, in cases where lava flows melt the ice from the surface downward, the main hazards are from localized phreatic explosions as opposed to potential flood/lahar hazards. However, when lava effusion/emplacement occurs beneath the ice surface, melting is more rapid and can produce lakes whose drainage could plausibly produce localized floods and lahars.

Evolution of the submarine–subaerial edifice of Bogoslof volcano, Alaska, during its 2016–2017 eruption based on analysis of satellite imagery - Christopher F. Waythomas; Kim Angeli; Rick L. Wessels (Bulletin of Volcanology, 2020)

Geology and eruptive history of Bogoslof volcano - Christopher F. Waythomas; Matthew Loewen; Kristi L. Wallace; Cheryl E. Cameron; Jessica F. Larsen (Bulletin of Volcanology, 2020)

Mechanisms for ballistic block ejection during the 2016–2017 shallow submarine eruption of Bogoslof volcano, Alaska - Christopher F. Waythomas; Larry G. Mastin (Bulletin of Volcanology, 2020)

Seismo-acoustic evidence for vent drying during shallow submarine eruptions at Bogoslof volcano, Alaska - David Fee; John Lyons; Matthew Haney; Aaron Wech; Christopher Waythomas; Angela K. Diefenbach; Taryn Lopez; Alexa Van Eaton; David Schneider (Bulletin of Volcanology, 2020)
Characterizing the state of the volcanic vent is key for interpreting observational datasets and accurately assessing volcanic hazards. This is particularly true for remote, complex eruptions such as the 2016–2017 Bogoslof volcano, Alaska eruption sequence. Bogoslof’s eruptions in this period were either shallow submarine or subaerial, or some combination of both. Our results demonstrate how low-frequency sound waves (infrasound), integrated with seismic and satellite data, can provide unique insight into shallow vent processes, otherwise not available. We use simple metrics, such as the infrasound frequency index (FI), event duration, and acoustic-seismic amplitude ratio, to look at changes in the elastic energy radiation and infer changes in seawater access to the vent. Satellite imagery before and after selected eruptions is used to ground-truth inferences on vent conditions. High FI and gradual increases in infrasound frequency content at Bogoslof correspond with transitions from submarine to subaerial vent conditions and a diminished or absent role of water, likely resulting in a drying out of the vent region. Event durations generally correlate with high FI and the range of FI values for each event, suggesting long duration events were more effective at drying out the vent region. A trend from low to high acoustic-seismic amplitude ratios for some long duration events also suggests an increase in acoustic efficiency as the vent dried out. We demonstrate that infrasound can serve as a robust indicator of seawater involvement for Bogoslof and other shallow submarine eruptions that may not be inferable from other datasets, particularly in near-real-time.

Petrology of the 2016–2017 eruption of Bogoslof Island, Alaska - Matthew W. Loewen; Pavel Izbekov; Jamshid Moshrefzadeh; Michelle Coombs; Jessica Larsen; Nathan Graham; Michelle Harbin; Christopher Waythomas; Kristi Wallace (Bulletin of Volcanology, 2019)

The 2016–2017 eruption of Bogoslof volcano, Alaska: preface to the special issue - Christopher F. Waythomas; John J. Lyons; David Fee; Kristi L. Wallace (Bulletin of Volcanology, 2019)

Organic matter quantity and source affects microbial community structure and function following volcanic eruption on K asatochi I sland, A laska - Lydia H. Zeglin; Bronwen Wang; Christopher Waythomas; Frederick Rainey; Sandra L. Talbot (Environmental Microbiology, 2016)
Summary In A ugust 2008, K asatochi volcano erupted and buried a small island in pyroclastic deposits and fine ash; since then, microbes, plants and birds have begun to re‐colonize the initially sterile surface. Five years post‐eruption, bacterial 16S r RNA gene and fungal internal transcribed spacer (ITS) copy numbers and extracellular enzyme activity ( EEA ) potentials were one to two orders of magnitude greater in pyroclastic materials with organic matter ( OM ) inputs relative to those without, despite minimal accumulation of OM ( C ). When normalized by OM levels, post‐eruptive surfaces with OM inputs had the highest β‐glucosidase, phosphatase, NAGase and cellobiohydrolase activities, and had microbial population sizes approaching those in reference soils. In contrast, the strongest factor determining bacterial community composition was the dominance of plants versus birds as OM input vectors. Although soil pH ranged from 3.9 to 7.0, and % C ranged 100×, differentiation between plant‐ and bird‐associated microbial communities suggested that cell dispersal or nutrient availability are more likely drivers of assembly than pH or OM content. This study exemplifies the complex relationship between microbial cell dispersal, soil geochemistry, and microbial structure and function; and illustrates the potential for soil microbiota to be resilient to disturbance.

The 2013 eruption of Pavlof Volcano, Alaska: a spatter eruption at an ice- and snow-clad volcano - Christopher F. Waythomas; Matthew M. Haney; David Fee; David J. Schneider; Aaron Wech (Bulletin of Volcanology, 2014)